PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERN AKUNTANSI TERHADAP KUALITAS DALAM PELAPORAN KEUANGAN DAERAH (Studi Empiris Pada BPKD Kabupaten Lumajang) - Nurmalia Nurmalia; Moh. Amin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine the effect of human resource capacity, use of information technology and internal accounting controls on the quality of regional financial reporting. The population in this study is BPKD Malang Regency. The method used in this research is quantitative research. Collecting data in this study by distributing questionnaires to BPKD employees of Lumajang Regency. The samples obtained were 64 respondents. This study uses multiple regression analysis. The results of this study are the simultaneous variable of human resource capacity, utilization of information technology and internal accounting controls have a significant influence on the quality of regional financial reporting. Partially the human resource capacity variable has a positive and significant effect on the quality of regional financial reporting. the use of information technology variables has a positive and significant effect on the quality of regional financial reporting. the internal control variable has a positive and significant effect on the quality of regional financial reporting.Keywords: Human Resources, Utilization of Technology, Internal Control, and Financial Reporting